Датчик для бесконтактного измерения температуры на основе волноводного кольцевого микрорезонатора - Goncharenko Игорь (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2010)
The possibility of applying the waveguide ring microresonators for remote sensing the temperature or power of IR radiation is shown. Sensitivity of the sensor on temperature can be as high as 0,01°, and on the power of IR radiation is 2,6 * 10-11 W, at that the range of temperature measurement is 100°. By using the radiation on 6 wavelengths it is possible to increase in 10 times the sensor sensitivity or its range of measurements. The response time of the receiver on IR signal power change (sensor speed) is 0,626 s.